2020
DOI: 10.1002/bio.3911
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the binding mode of donepezil with calf thymus DNA using spectroscopic and molecular docking methods

Abstract: Donepezil (DNP) is one of approved drugs to treat Alzheimer's disease (AD). However, the potential effect of DNP on DNA is still unclear. Therefore, the interaction of DNP with calf thymus DNA (DNA) was studied in vitro using spectroscopic and molecular docking methods. Steady‐state and transient fluorescence experiments showed that there was a clear binding interaction between DNP and DNA, resulting from DNP fluorescence being quenched using DNA. DNP and DNA have one binding site between them, and the binding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…At optimum experimental conditions, linear Stern‐Volmer quenching plots (Figure 3B) at 298, 303 and 313 K showed only a uniform quenching process. In the study, decreasing K sv values with increasing temperature confirms that quenching is static, while a reverse trend is obtained for the dynamic quenching mode [17,28,29] …”
Section: Resultsmentioning
confidence: 55%
See 1 more Smart Citation
“…At optimum experimental conditions, linear Stern‐Volmer quenching plots (Figure 3B) at 298, 303 and 313 K showed only a uniform quenching process. In the study, decreasing K sv values with increasing temperature confirms that quenching is static, while a reverse trend is obtained for the dynamic quenching mode [17,28,29] …”
Section: Resultsmentioning
confidence: 55%
“…In the study, decreasing K sv values with increasing temperature confirms that quenching is static, while a reverse trend is obtained for the dynamic quenching mode. [17,28,29] These values demonstrated that the affinity of OFL on fsDNA was weak, and the stability of the association with fsDNA declined upon the temperature increment. K value of OFL on fsDNA was significantly lower than that of the typical intercalator (such as K = 1.4 × 10 6 M À 1 for EtBr) though it fell within the range of the binding constant of groove…”
Section: Chemistryselectmentioning
confidence: 95%
“…As the fluorescence quenching was a static mechanism, the binding constants ( K a ) and the number of binding site (n) could be obtained using Equation (6), originated from a previous report (Figure 5) [ 48 ] : italiclogF0FFgoodbreak=italiclogKagoodbreak+italicn.35emitaliclog[]Q Binding constants between ligands and proteins can be significant parameters to estimate the interaction effects in terms of binding behaviours. Generally, K a values in the range 10 4 –10 6 M −1 imply that proteins and ligands are able to bind in vivo .…”
Section: Resultsmentioning
confidence: 99%
“…As the fluorescence quenching was a static mechanism, the binding constants (K a ) and the number of binding site (n) could be obtained using Equation ( 6), originated from a previous report (Figure 5) [48] :…”
Section: Confirmed the Binding Informationmentioning
confidence: 99%
“…The fluorescence spectrum of resorcinol consists of two excitation peaks at 217 nm and 272 nm, respectively, and one emission peak at 304 nm (Figure 2a). To determine the most suitable excitation wavelength, the quenching effects of DNA on resorcinol fluorescence were recorded at the different excitation wavelengths [34] (Figure 2b, c). The degree of fluorescence quenching at 272 nm was more obvious than that at 217 nm (Figure 2d).…”
Section: Fluorescence Experimentsmentioning
confidence: 99%